Melody and chord discrimination of cochlear implant users in different pitch ranges. (November 2013) - Boeckmann-Barthel, Martin; Ziese, Michael; Rostalski, Dorothea; Arens, Christoph; Verhey, Jesko Lars
Abstract : Objective: The study assesses the ability of cochlear implant (CI) recipients to discriminate music excerpts, namely melodies and chords. Natural instrument recordings were used to test whether an improved fine-structure transmission is beneficial for this task at low pitches. Methods: Seventeen CI recipients using either a continuously interleaved strategy (CIS) strategy or fine-structure coding (FSP) had to discriminate melody pairs played by the violin or the cello, and pairs of chords differing at high or low pitches. The examples were taken from the Mu.S.I.C. perception test. Results: In the melody task, no differences were found according to pitch range or processing strategy. In the chords task, changes in the low-pitch range provided a significantly greater difficulty for CI recipients using the CIS stategy and correct detection was reduced by 11.1% compared to the detection of high-pitch changes. This drop in performance was reduced in the FSP users to 7.4% correct and was statistically not significant. Conclusions: When musical chords played with natural instrument are discriminated by CI users, a fine-structure coding strategy provides some benefit at low pitches. No benefit was found in the discrimination of unaccompanied melodies.